Bioactive potential of Lagotis cashmeriana: a study on morphology, phytochemicals, and antioxidant activity - Mohidin, Rumaisa; Ganie, Showkat Ahmad; Shiekh, Farooq A.; Malik, Akhtar H.; Bhat, Owais Mohmad; Dar, Abid Hamid; Qureshi, Shabir H.; Wani, Nissar Ahmad; Zargar, Mohammad Afzal (Natural product research, 2025)
The present study aimed to investigate the morphological features, phytochemicals, phenolic content, and antioxidant activity in different parts of Lagotis cashmeriana. The morphological features depicted that the plant is 7.9 ± 1.699 cm tall with flowers arranged into an inflorescence. The length of inflorescence was 2.597 ± 0.796 cm. Basal leaves were measuring 2.99 ± 0.58 cm. Besides, the number of basal leaves and inflorescence ranged from 4-9 and 0-4 respectively. Methanolic extract of leaves displayed the highest phenolic content (169.5 µg/mL of GAE), followed by inflorescences (157 µg/mL of GAE). Among aqueous extracts, leaves displayed the highest phenolic content (88.38 µg/mL of GAE), followed by inflorescences (76.95 µg/mL of GAE). The results of antioxidant study revealed that the methanolic extracts of leaves possessed the highest antioxidant potential (180.76 µg/mL of AAE). Interestingly, for each extract, there was a positive correlation between the phenolic content and the antioxidant activity.